Public health significance of dental fluorosis among 12-15 years old school children in Zeway, Oromia Region, Ethiopia - Gebretsadik, Heron Gezahegn (Orapuh Journal, 2021)
Introduction While fluoride is accepted as being effective in the prevention of dental caries, the excessive consumption of fluoride can put bones and teeth at risk of developing fluorosis. Dental fluorosis is a condition affecting teeth and is caused by an increased intake of fluoride over an extended period during tooth development. Fluoride ingested through drinking water during dental development, until the age of six, may promote the development of fluorosis. Purpose The purpose of this study was to assess the public health significance of dental fluorosis among 12-15 years old school children in Zeway, Oromia Region, Ethiopia Material and Methods A descriptive cross-sectional study was conducted between June 5, 2018, and July 9, 2018. A total of 1290 school children, aged 12 – 15 years participated in the study. The public health significance of dental fluorosis among the study participants was measured by using the community fluorosis index catalog. Result The community fluorosis index of the total population studied was 2.02, which denotes the ‘Marked’ public health significance of the condition. The public health significance of dental fluorosis increased with increasing distance away from the city center. The community fluorosis index score of the rural population studied was the highest (2.76 ) compared to the scores of semi-urban (2.26) and urban (1.76) samples, respectively. Conclusion Dental fluorosis is a major public health problem in the study population. Beside the general intervention, more attention needs to be given to the semi-urban and rural communities to identify the risk factors of dental fluorosis in the areas and eliminate or modify them to mitigate the prevalence of this oral health problem in the study population.